Improvement of the productivity by increasing customer outputs at cafeteria on campus via simulation method in witness - Lee, Kim Sim (2009)
In this thesis, the importance of productivity improvement was displayed by conducting a research in a company to increase the company's output. The whole project was carried out by using simulation method as a tool to mimic the actual layout which then productivity improvement strategies could be determined. The simulation software used in this project is WITNESS simulation software which could display the current performance of outputs and the service floor layout. The main objective of this project is to evaluate existing service floor performance, then design and improve floor layout by using simulation software and followed by measuring performance such as output quantity by using cost effectiveness analysis. In this project, the study is conducted at Sarikim Enterprise which is also known as the Café Executive in Universiti Malaysia Pahang. The process flow was observed once the customer enters the system until the customer purchase the food and beverages before leaving the system. Initially, a simulation model is built to study the existing actual floor layout and found out there are stations that are taking too much time for process. After that, a total of 3 options were proposed to solve the problem and at the same time increase the customer outputs. Non parametric Kruskal-Willis test were conducted and the results showed there is a significant difference between the layouts. In order to choose the best layout, one way ANOVA test with multiple comparison was used and the best option is Option 3 which is addition of Dishes station and merging of the Plate and Rice station provided and extra costs of RM720 were needed. However, by conducting the cost effectiveness analysis, although extra costs are needed for the new layout, the cost estimated for 1 customer is less than the actual layout. This also proved that Option 3 is the most suitable propose layout to increase the productivity.